Ethics Using Personal data for Personalized advertising: Literature Review and Research Agenda - Lina, Lia; Fuzail, Muhammad; Iswanto, Dedy (TECHNOBIZ : International Journal of Business, 2026)
Online advertising systems use the principle of customer-based targeting. It’s called Personalized advertising. Personalized advertising is closely related to personal data. So, the ethical dilemma in personalized advertising has been discussed in existing research and becomes a paradox. This study conducted a literature review by analyzing articles from the Scopus database period of 2004-2023 (20 years). This research aims to define Personalized Advertising, explain the Ethical Dilemma, and summarize the Empirical findings. The findings of the literature review are presented in several parts. First, there are various definitions of personalized advertising. Second, the distribution of articles was published in reputable journal, and an overview of the empirical findings from various research was then suggested for future research and policymakers to avoid the ethical dilemma.